P4.045 When Talking or Not Talking Becomes a Risk: A Grounded Theory Study Exploring the Impact of HIV on Immigrant Black African Families in the UK. (13th July 2013) - Owuor, J O A; Locke, A; Heyman, B
Abstract : Background: Black Africans, culturally very diverse, make up less than 1% of the UK population. Yet they are the single most affected heterosexual group by HIV, accounting for a third of all annual new HIV diagnoses. Advancements in HIV treatment have transformed HIV into a chronic illness. Thus, families now deal with long term implications of HIV. In the UK, HIV testing, and more recently treatment, is free. Yet, black Africans predominantly test very late for HIV hence more susceptible to HIV-related morbidity and mortality. This paper explores the participants' risk perceptions, particularly men, on what it means to live with diagnosed HIV and the views of service providers on how the services can respond. Methods: This paper is based on a qualitative study involving in-depth interviews with 23 participants; 11 positive men, 6 positive women, 1 negative man and 5 employees of HIV service-provider agencies. Data analysis was based on grounded theory's cyclic three-stage process; open coding, axial coding and selective coding. Results: The men and their partners rarely discussed their positive diagnosis with other family members, because they feared losing control over whom else would know about their diagnosis through a 'cascade of disclosure'. Although disclosure is a pre-requisite for seeking support, many participants shunned potential support rather than risk stigmatisation. Men were particularly reluctant to discuss their HIV status with other family members, and were more at risk of exposure. 83% of the men and 50% of the women had been exposed by a third party. Conclusions: Communication about HIV in the family, in a complex multicultural context, remains a challenge. This inhibits family members' access to and use of HIV services, contributing to continued poor outcomes for immigrant black Africans, particularly the men. This in turn diminishes the potential of the current positive prevention campaigns.